Temporal change in bimanual interkeypress intervals and self-reported symptoms during continuous typing. - Liang H; Hwang Y; Chang F (Journal of Occupational Rehabilitation, 2008)
Introduction: Continuous typing is likely to induce mental and/or muscular fatigue, which contributes to musculoskeletal discomfort. Our goals were to describe the temporal changes in symptoms and interkeypress intervals (IKIs) of each hand during continuous typing. The effects of demographic characteristics and time on the IKI were examined. Methods: Twenty-four healthy and skilled typists volunteered to participate in this repeated-measurement study. All the subjects typed an English text for 90 min in the laboratory. The outcomes included self-reported pain and fatigue, average typing speed, accuracy rate, finger tapping speed, and IKIs as recorded by electronic activity monitoring software (VDTlog). The changes in self-reported symptoms, average typing speed and accuracy rate after 90 min of typing were compared with baseline data by paired testing. The effects of demographic characteristics and time on IKIs of both hands were explored by generalized estimate equation (GEE) analysis. Results: The pain and fatigue ratings of the study subjects were significantly higher after 60 and 90 min of typing, but the average typing speed of every 30 min remained similar. The most common complaints were associated with the eyes, upper back and wrists. The IKIs as recorded by VDTlog was associated with typing speed. Furthermore, GEE analysis showed that the IKI of the right hand was the shortest in the last 10 min throughout the experiment, while left-hand typing exhibited the longest IKI during the last 10 min of each 30-min typing session. Conclusion: Time has different effect on the temporal changes of IKI during continuous typing for the left and right hands. Right-hand IKI tends to be shorter by time, especially at the last 10 min of typing, while left-hand IKI prolongs as typing continues for 30 min. Perceived pain and fatigue is apparent after continuous typing, though no change in average typing speed is observed.